Interfacial intermetallic compound modification to extend the electromigration lifetime of copper pillar joints - Yang, Dongsheng; Huang, Yilong (Frontiers in Materials, 2023)
Electromigration is the massive metal atom transport due to electron flow, which could induce a disconnect in electronics. Due to the size of copper pillar bump reduction, the portion of interfacial intermetallic compound in solder joints is increasing obviously. However, there is lack of systematical research on the effects of intermetallic compound on the EM lifetime of solder joints. In this paper, the interfacial intermetallic compound of copper pillar joints is modified to extend the electromigration lifetime. The growth rate of intermetallic compound in solder joints sample is calculated firstly. From 230°C to 250°C, the growth rate of intermetallic compound increases from 0.09 μm/min to 0.19 μm/min. With a longer reaction time, the intermetallic compound layers continuously grow. Then electromigration tests were conducted under thermo-electric coupling loading of 100°C and 1.0 × 104 A/cm2. Compared with lifetime of thin and thick intermetallic compound samples, the lifetime of all intermetallic compound sample improved significantly. The lifetime of thin, thick, and all intermetallic compound samples is 400 min, 300 min, and 1,200 min, respectively. The failure mechanism for the thin intermetallic compound sample is massive voids generation and aggregation at the interface between solder joints and pads. For the thick intermetallic compound sample, the intermetallic compound distance is short between cathode and anode in solder joints, leading to lots of crack create in the middle of solder joints. As the all intermetallic compound sample can greatly reduce the number of voids generated by crystal structure transforming, the lifetime extend obviously.